1, 25(OH)2D3 attenuates sleep disturbance in mouse models of Lewis lung cancer, in silico and in vivo. Issue 11 (1st June 2021) - Ai, Min; Li, Shuang‐shuang; Chen, Hong; Wang, Xi‐ting; Sun, Jiang‐nan; Hou, Bao; Cai, Wei‐wei; Zhou, Yue‐tao; Qiu, Li‐ying
Abstract: Many clinical studies have reported that patients diagnosed with cancer will suffer from sleep disturbance during their clinical process, especially among lung cancer patients, and this effect will not easily subside. 1, 25‐dihydroxy‐vitamin‐D3 [1, 25(OH)2 D3 ], the activated form of vitamin D, can participate in neuronal differentiation and prevent damage to the nervous system. However, little is known about the potential therapeutic effects of cancer‐related psychiatric symptoms. In light of this, we hypothesized that a low circulating level of vitamin D was related to sleep quality in the presence of a tumor, 1, 25(OH)2 D3 may be an effective way to ameliorate sleep disturbance and neurochemical alterations along with the cancer progress. Male C57BL/6 mice were implanted with intracranial transmitters to monitor electroencephalogram and were subcutaneously inoculated with Lewis lung cancer cells. The results demonstrated that on Days 19–20, tumor‐bearing mice displayed fragmented sleep, shortened wake phase, prolonged sleep in the non‐rapid eye movement phase, and the levels of vitamin D‐associated genes in the brain had changed a lot compared to control mice. Importantly, 1, 25(OH)2 D3 treatment really effectively saved the sleep quality of tumor‐bearing mice. We further explored and confirmed that 1, 25(OH)2 D3 repressed tumor‐induced neuroinflammation (IL‐1β, TNF‐α, IL‐6, IL‐10, IFN‐γ, and IL‐2), enhanced neurotrophic factors (brain‐derived neurotrophic factor [BDNF], glialcellline‐derived neurotrophic factor) and 5‐HT system in the hippocampus, hypothalamus or cortex. A molecular docking approah manifested the ability of 1, 25(OH)2 D3 to affect the activity of tryptophan hydroxylase 2 and BDNF. Together, our results suggested that 1, 25(OH)2 D3 treatment may attenuate sleep disturbance in Lewis lung cancer‐bearing mice, and become a promising strategy for treating cancer symptom clusters to ameliorate the quality of life of patients with cancer. Abstract : Lewis lung cancer‐bearing mice displayed fragmented sleep, shortened wake phase, and prolonged sleep in the non‐rapid eye movement (NREM) phase. 1, 25(OH)2D3 treatment effectively saved the sleep quality of tumor‐bearing mice. 1, 25(OH)2 D3 repressed tumor‐induced neuroinflammation, enhanced neurotrophic factors, and 5‐HT system. A molecular docking approach manifested the ability of 1, 25(OH)2D3 to affect the activity of TPH2 and brain‐derived neurotrophic factor (BDNF).